Hello, I'm stuck in solving this problem where I got to prove this equation with induction. Got problems with the 1st step already x.x On the 1st step, do I have to prove the equation for n=0 or n=1 on the following problem? How and why? On the 2nd step for n=m I know what to do... But then I'm again stuck on the 3rd step, for n=m+1, I don't know how to transform the trigonometry forms on the left side of the equation to make it the same as the right side. I'd appreciate any help or explanation. Thanks in advance. The problem is: